The Development of Realistic Mathematics Education Based Learning Tools to Improve Mathematical Problem Solving Ability and Self-Efficacy on Students in Junior High School 1 Lubuk Pakam - Delima Manurung; P. Siagian; Ani Minarni (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
This study aims to 1) Produce the valid, practical, and effective of Realistic Mathematics Education based learning tools; 2) Analyzing the improvement of students' mathematical problem solving ability that are learned using Realistic Mathematics Education-based learning tools; and 3) Analyzing the achievement of students' self-efficacy who are taught using Realistic Mathematics Education-based learning tools. The subjects in this study were seventh grade students of Junior High School 1 Lubuk Pakam. Data collection instruments in this development are assessment instruments to assess the products that have been developed. In addition, students were given questionnaires to get data about students' Self-Efficacy. This research is Research and Development with the design of learning development models by Dick and Carey. The steps include: 1) Conducting preliminary research; 2) Making software design; 3) Collecting the materials; 4) Developing the contextual based interactive multimedia; 5) Product reviews and trials; and 6) the effectiveness of product test. The results showed Realistic Mathematics Education-based learning tools on students' mathematical problem solving ability increased from trial I to trial II with an average increase per indicator of 0.35%; 3.99%; 16.22% and 8.32%. The developed learning tool has fulfilled the effective criteria, namely the mastery learning of students classically in the first trial has reached a good category and in the second trial has reached a very good category; the achievement of student learning goals during learning activities meet the ideal criteria specified; student responses is positive to the components of learning tools and learning activities developed; and the allocation of ideal time usage.